2012
DOI: 10.1890/11-1750.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrient supply modulates temperature‐induction cues in mast‐seeding grasses

Abstract: Abstract. Synchronous and intermittent reproduction in long-lived plants, known as mast seeding, is induced by climatic cues, but the mechanism explaining variation in masting among neighboring but edaphically segregated species is unknown. Soil nutrients can enhance flowering, and thus, populations on nutrient-rich soils may require less-favorable growing temperatures to flower. We tested this hypothesis by predicting the probability of flowering in response to air temperature for five species of alpine Chion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 40 publications
6
67
0
Order By: Relevance
“…teretifolia soils, which have a higher C:N ratio compared to C . pallens soils [33]. Actinobacterial abundance in soil was previously positively correlated with total microbial biomass and C:N ratio in grassland soils [35,64].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…teretifolia soils, which have a higher C:N ratio compared to C . pallens soils [33]. Actinobacterial abundance in soil was previously positively correlated with total microbial biomass and C:N ratio in grassland soils [35,64].…”
Section: Resultsmentioning
confidence: 99%
“…Diversification within this group resulted in more than 10 species in the region segregated according to altitude, soil conditions and snow lie [30,31]. The edaphic segregation of species influences temperature cues, flowering intensity, costs of seed production and vegetative growth [32,33]. Different species of Chionochloa exhibit adaptation to different extremes in natural soil fertility, resulting in distributions that are delimited by soil nutrients [30,32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sala et al 2012;Ichie and Nakagawa 2013). Moreover, Tanentzap et al (2012) showed the positive correlation between soil nitrogen and the mean probability of flowering for five species of Chionochloa in New Zealand. This model contained regions of parameter space that demonstrated constant, intermittent and chaotic seedfall regimes and was shown to demonstrate synchronicity under coupling through pollen limitation.…”
Section: Introductionmentioning
confidence: 86%